Application of Yokohama system for reporting breast Fine Needle Aspiration Cytology in correlation with histopathological and radiological findings - Apuroopa, Murari; Chakravarthy, V Kalyan; Rao, D Ranga (Annals of Pathology and Laboratory Medicine, 2020)
Background: Breast cancer is the leading cause of cancer deaths among women worldwide. Fine needle aspiration cytology (FNAC) and breast ultrasound are pivotal in characterization of a breast lump as benign and malignant lesion. The main objectives were to categorise the Breast FNAC samples according to new system of reporting and to assess the Risk of malignancy (ROM), sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and diagnostic accuracy for all categories. Methods: A Total of 900 FNAB cytology specimens from January 2017 to December 2018 were obtained. These were reclassified according to newly proposed IAC Yokohama system of reporting. The ROM, sensitivity, specificity, Positive Predictive Value (PPV), Negative Predictive Value (NPV) and diagnostic yield of Breast FNAC and also of ultrasound were calculated. Result: Among 900 cases, 4.3% fall in category 1, 58%- category 2, 17.7%- category 3, 7.2%- category 4 and 12.8% - category 5, and correlated with corresponding radiological impression. Sensitivity, specificity, PPV, NPV and diagnostic accuracy of ultrasound were respectively 91.6%, 96.8%, 95.6%, 92.8%, 91.5% and those of FNAC respectively 94.59%, 98.9%, 98.59%, 95.74%, 96.97%. ROM is 5.0% for category 1, 1.2% for category 2, 12.5% for category 3, 93.65% for category 4 and 100% for category 5. Conclusion: IAC Yokohama system of reporting breast cytopathology serves as a common language to pathologist and clinician. Breast ultrasound is a non-invasive imaging-based technique and both these diagnostic tools can complement each other for patient diagnosis and management.